The Existence of Islamic Politics Against Heterodox of Islamic Movements in Indonesia: Post-Independence Rifa'iyah Sect - Bahriyah, Amalina Zukhrufatul; Rohman, Moh. Mujibur; Ilahi, M. Ridho; Mahrus, Ahmad; Aulia, Muhammad Izzul; Akbar, Muhammad Syarif Hidayatullah (AJIS: Academic Journal of Islamic Studies, 2024)
This research explains the relationship between politics and Islamic movements which influence each other with their respective roles in society. Political discussions include power, ideology, legitimacy, government, state, nation and others. The political consequences have had a huge impact on the orthodoxy and heterodoxy of the Islamic movement in Indonesia. This study focuses on the Rifa'iyah case in the 20th century AD. The Rifa'iyah group is heterodox because it is considered to deviate from Islamic teachings in general. This causes heterodox groups to experience discrimination and prohibitions from the Central Java Prosecutor's Decree. The uniqueness of Rifa'iyah's living pattern is in groups and in rural areas. This minority group received political asylum and blended into society until their struggle succeeded in revoking the prohibition decree. Especially the emergence of reform which has become the political aspirations of the Islamic community. This research is a qualitative type using a social-historical approach. The data collection method is library research, while the data analysis method is descriptive analysis. The research results show that politics has a role as accommodative, hegemonic and power. Rifa'iyah's strategy is to adjust its political role to regain its legality by collaborating with political parties, studying academically by holding seminars, and taking advantage of the reform period. The existence of politics can dissolve or maintain heterodox.